(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
A "bloodhound" at the “Last Supper”: religious references in commercial communication under scrutiny by the Italian Advertising Self-Regulation Institute ABSTRACT: Since the birth of commercial advertising there has been a widespread use of religious references in the creation of promotional material, in some cases even distorting, trivializing, or exploiting the representations of the Sacred symbols. So, it is important to properly to understand whether and within what limits the use of religious references in advertising should be admitted, as well as the possible protection that can be granted to religious sentiment which may be harmed by such use. Starting from the recent case relating to the segugio.it commercial, this contribution examines the issue with regard to the provisions contained in an important soft law instrument of the Italian legal system, i.e. the Advertising Self-Regulatory Code, and the rulings made in its application by the decision-making bodies of the Advertising Self-Regulation Institute. SOMMARIO: 1. I riferimenti religiosi nella pubblicità commerciale - 2. La disciplina italiana della pubblicità commerciale in relazione al sentimento religioso e il Codice di Autoregolamentazione della Comunicazione Commerciale - 3. Il concetto di offesa al sentimento religioso delineato dalle pronunce dell’I.A.P. - 4. I precedenti “usi” pubblicitari dell’Ultima Cena - 5. Un tentativo di conclusione.